Underwater Acoustic Ecology Metrics in an Alaska Marine Protected Area Reveal Marine Mammal Communication Masking and Management Alternatives - Gabriele, Christine M.; Ponirakis, Dimitri W.; Clark, Christopher W.; Womble, Jamie N.; Vanselow, Phoebe B. S. (Frontiers in Marine Science, 2018)
Vessel-generated underwater noise can affect humpback whales, harbor seals and other marine mammals by decreasing the distance over which they can communicate and detect predators and prey. Emerging analytical methods allow marine protected area managers to use biologically relevant metrics to assess vessel noise in the dominant frequency bands used by each species. Glacier Bay National Park (GBNP) in Alaska controls summer visitation with daily quotas for vessels ranging from cruise ships to yachts and skiffs. Using empirical data (weather, AIS vessel tracks, marine mammal survey data and published behavioral parameters) we simulated the movements and acoustic environment of whales and seals on three days with differing amounts of vessel traffic and natural ambient noise. We modeled communication space (CS) to compare the area over which a vocalizing humpback whale or harbor seal could communicate with conspecifics in the current ambient noise environment (at 10-min intervals) relative to how far it could communicate under naturally quiet conditions, known as the reference ambient noise condition (RA). RA was approximated from the quietest 5th percentile noise statistics based on a year (2011) of continuous audio data from a hydrophone in GBNP, in the frequency bands of whale and seal sounds of interest: humpback “whup” calls (50-700 Hz, 143 dB re 1 µPa source level, SL); humpback song (224-708 Hz, 175 dB SL), and harbor seal roars (40-500 Hz, 144 dB SL). Results indicate that typical summer vessel traffic in GBNP causes substantial CS losses to singing whales (reduced by 13-28%), calling whales (18-51%) and roaring seals (32-61%), especially during daylight hours and even in the absence of cruise ships. Synchronizing the arrival and departure timing of cruise ships did not affect CS for singing whales, but restored 5 – 12% of lost CS for roaring seals and calling whales, respectively. Metrics and visualizations like these create a common currency to describe and explore methods to assess and mitigate anthropogenic noise. Important next steps toward facilitating effective conservation of the underwater sound environments will involve putting modeling tools in the hands of marine protected area managers for ongoing use.